Interpretacija vidovyh različij meždu russkim, češskim i slovenskim jazykami - Petruhina, Elena Vasil'evna (Slavistična revija, 2019)
The article offers an explanation of the differences in aspectual usage in Russian, on the one hand, and Czech and Slovenian, on the other. The language data analyzed in this research confirm the assumption that the profiling of the categorial concept of perfective and imperfective differs in the languages in question. The idea of totality in the category of aspect has a more significant value in Czech and Slovenian, while in Russian it is the idea of time limit or border that is more important. The given concept in Russia - in contrast to Czech and Slovenian - is distinct in the perfective grammeme (including in derived verbs with inceptive prefixes, in delimitatives with the prefix po, saturatives with the formants na- -sja, etc). This affects the usage and collocation of perfective verbs, as well as the organization of aspectual opposition and the degree of markedness of perfective and imperfective aspect.
Keywords: aspect; celostnost; Czech; češčina; glagolski vid; limit; meja; Russian; ruščina; Slovenian; slovenščina; totality